Factors affecting entrepreneurial intention for sustainable tourism among the students of higher education institutions - Danish Mehraj; Muhammad Idrees Ul Islam; Ishtiaq Hussain Qureshi; Shakeel Basheer; Mubashir Majid Baba; Viqar u Nissa; Mohd Asif Shah (Cogent Business & Management, 2023)
Entrepreneurs have an essential role to play in bringing positive change and growth to the world's economy. Entrepreneurship is a necessary aspect of economic growth because of its contribution to people's welfare through employment opportunities. Likewise, institutions of higher learning offer compulsory entrepreneurship courses for students with the support of government policies to encourage students towards entrepreneurship. Therefore, this study aimed to determine the factors influencing the students' intentions to become green entrepreneurs. The study uses the extended theory of planned behaviour model (TPB) and entrepreneurial education to develop a theoretical framework. The model has been examined on 350 tourism university students using structural equation modelling. The key findings indicate that Ajzen's TPB theory of planned behaviour and entrepreneurial education can be extensively expanded to determine sustainable entrepreneurial intentions in developing economies such as India. Attitude, subjective norms, perceived behavioural control, and entrepreneurial education are antecedents of entrepreneurial intent. Our results have valuable implications for aspiring entrepreneurs, policymakers, and scholars.
Keywords: 650; attitude; entrepreneurial education; entrepreneurial Intentions; perceived behavioural control; subjective norm; sustainable entrepreneurship; theory of planned behaviour